Term pregnancy with large anterior wall intramural fibroid: an intra-operative challenge - Mehrotra, Seema; Singh, Urmila; Solanki, Vandana; Shanker, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Leiomyomas are the most common benign smooth muscle tumors of the uterus. The incidence during pregnancy ranges between 1.6 to 10%. The management of fibroids encountered during caesarean section poses a therapeutic dilemma. We present a case of giant anterior wall lower segment leiomyoma complicating term pregnancy which posed a great surgical challenge. Myomectomy was performed before delivering the baby by lower segment caesarean section by locating the tumor free area using preoperative ultrasound. The tumor mass weighed 3kg. This case highlights the preoperative use of ultrasound in emergency caesarean section to avoid classical caesarean section and to prevent fetal mortality and morbidity by avoiding time consuming caesarean myomectomy before the delivery of the baby.